2012
DOI: 10.1182/blood-2011-06-359075
|View full text |Cite
|
Sign up to set email alerts
|

Trisomy 12 and elevated GLI1 and PTCH1 transcript levels are biomarkers for Hedgehog-inhibitor responsiveness in CLL

Abstract: Hedgehog (HH) signaling is activated in various lymphoid malignancies, but conflicting results exist about its role in chronic lymphocytic leukemia (CLL). Here, we demonstrate that the expression of essential HH pathway components like GLI1, PTCH1, and the HH ligands is highly diverse in CLL. A subset of 36.7% of 60 tested CLL samples responded to all 3 SMOOTHENED (SMO) inhibitors, whereas 40% were completely resistant. Responsiveness correlated with elevated GLI1 and PTCH1 transcript levels and the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 52 publications
1
33
0
Order By: Relevance
“…Recent evidence for constitutive Hh activation was observed in models of small and non-small cell lung cancer, melanoma, and chronic myelogenous and lymphocytic leukemia, in which the pathway is activated in the tumor cells (36)(37)(38)(39)(40). However, the presence of transcripts for Hh target genes does not necessarily represent active signaling, without evidence that the expression can be modulated by pathway inhibition (35,41).…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence for constitutive Hh activation was observed in models of small and non-small cell lung cancer, melanoma, and chronic myelogenous and lymphocytic leukemia, in which the pathway is activated in the tumor cells (36)(37)(38)(39)(40). However, the presence of transcripts for Hh target genes does not necessarily represent active signaling, without evidence that the expression can be modulated by pathway inhibition (35,41).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, trisomy 12 CLL cells produced DHH, suggesting that autocrine signaling may be important in this subtype. 98 Hh has been implicated in the etiology of T-cell lymphomas. Singh et al demonstrated that constituents of the Hh pathway were overexpressed in ALK ϩ anaplastic large cell lymphoma.…”
Section: Lymphoma and Cllmentioning
confidence: 99%
“…They found that 60% of their CLL cohort responded to SMO inhibition. 98 Factors that predicted likelihood of response included elevated expression of GLI1 and PTCH1 and carriage of trisomy 12. In addition, trisomy 12 CLL cells produced DHH, suggesting that autocrine signaling may be important in this subtype.…”
Section: Lymphoma and Cllmentioning
confidence: 99%
“…The interaction between BMSCs and CLL cells induces a protective microenvironment blocking the proapoptotic effect of various chemotherapeutical agents and spontaneous apoptosis in vitro. Pathways involved in this process are the CXCL12-CXCR4 axis, Hedgehog (HH) ligands activating the HH signaling pathway in CLL cells, and various other chemokines and integrins (12,16,43). To evaluate the effect of protective stromal cells on the effect of PIM kinase inhibitors in CLL, we cocultured CLL cells with the BMSC line M2-10B4 (base line viability with and without stroma is shown in Supplementary Fig.…”
Section: Pim Kinase Inhibition With Three Different Pim Inhibitors Inmentioning
confidence: 99%